When Art Meets Business: The Role of Identity Salience in Shaping Decisions and Success in the Creative Industries - Crezee,Rosalie; Boogers,Merel (2025)
There is still limited understanding of how entrepreneurial identity evolves over time and what the consequences of such changes are. Entrepreneurs in the creative industry is an interesting field to study identity work due to the ongoing tension between the commercial drive for growth and financial success and the creative pursuit of artistic authenticity and expression. This study, refers to these two role identities as the ‘artistic identity’ versus the ‘entrepreneurial identity’. This study explores how these two identities shift in salience, becoming more or less dominant, in different contexts. To understand what triggers these transitions, it is crucial to examine when and why these two identities become dominant over time, and how this influences entrepreneurial decision-making and perception of success. A qualitative research method was applied by interviewing thirteen participants. The findings suggest that a ‘safety threshold’, explains the constant interplay between these two identities and its impact on decision-making. The safety threshold is defined by the authors as a subjective tipping point where emotional discomfort (e.g., loss of authenticity) or financial insecurity surpasses a tolerable level, prompting a transition in the salient identity role. Thus, the Salience–Identity–Adaptation Cycle has been proposed as an interpretive framework to describe the recursive nature of these dynamics. This study contributes to theory and practice by introducing a new framework that offers a nuanced view on how entrepreneurs in the creative industry balance these two identities throughout their entrepreneurial journey.